2022
DOI: 10.1038/s41598-021-04248-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and network analysis highlight potential pathways in the pathogenesis of pterygium

Abstract: Pterygium is a common ocular surface condition frequently associated with irritative symptoms. The precise identity of its critical triggers as well as the hierarchical relationship between all the elements involved in the pathogenesis of this disease are not yet elucidated. Meta-analysis of gene expression studies represents a novel strategy capable of identifying key pathogenic mediators and therapeutic targets in complex diseases. Samples from nine patients were collected during surgery after photo document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Notably, pterygium is referred to as an "ophthalmic enigma" [4] because it represents a multifactorial disease as a result of a multitude of risk factors, including inflammation [5][6][7], antiapoptotic growth and proliferative mechanisms [8,9], angiogenic factors [10,11], oxidative stress and hypoxic ischemic injuries [12,13], viral infections [14], and extracellular matrix remodeling [15]. However, there is scientific consensus in the perception of pterygium as one of the most common sun-related eye diseases (ophthalmohelioses) [16], with UV-B playing a key role through inducing oxidative stress and is responsible for phototoxic DNA damage [17,18].…”
Section: Of 14mentioning
confidence: 99%
“…Notably, pterygium is referred to as an "ophthalmic enigma" [4] because it represents a multifactorial disease as a result of a multitude of risk factors, including inflammation [5][6][7], antiapoptotic growth and proliferative mechanisms [8,9], angiogenic factors [10,11], oxidative stress and hypoxic ischemic injuries [12,13], viral infections [14], and extracellular matrix remodeling [15]. However, there is scientific consensus in the perception of pterygium as one of the most common sun-related eye diseases (ophthalmohelioses) [16], with UV-B playing a key role through inducing oxidative stress and is responsible for phototoxic DNA damage [17,18].…”
Section: Of 14mentioning
confidence: 99%
“…Despite today's technological conditions, research into the development of effective drugs for pterygia is progressing at a slower pace because the formation of pterygia is highly complicated. Its complete etiology is still unknown (De Guimarães et al., 2022; Liu et al., 2023) Using microarray or high‐throughput sequencing technology, previous studies have demonstrated that mRNA, miRNA, and lncRNA dysregulation is mainly associated with extracellular matrix organization, blood vessel morphogenesis, and focal adhesion (De Guimarães et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pterygium is a fibrovascular degenerations of the conjunctiva that extends into the corneal limbus [ 1 ]. It can cause significant damage to visual function, triggering irritation [ 2 ], inflammation [ 3 ] and astigmatism [ 4 ]. Currently, there is no effective drug or conservative treatment for advanced pterygium, and surgery remains the best treatment option.…”
Section: Introductionmentioning
confidence: 99%